A compact, dual-polarized patch antenna with improved Tx–Rx isolation for 2.4 GHz single frequency full-duplex applications. Issue 3 (13th April 2021) - Nawaz, Haq; Basit, Muhammad Abdul; Niazi, Ahmad Umar
Abstract: A compact dual-polarized monostatic antenna (single radiator for transmit and receive modes) is presented with differential receive mode operation to achieve excellent interport isolation for 2.4 GHz single frequency full-duplex or in-band full-duplex applications. The presented antenna comprises three ports radiating element (patch) and a simple 3 dB/180 o ring hybrid coupler has been utilized for differentially excited receive mode operation. The 3 dB/180 o ring hybrid coupler acts as a self-interference cancellation (SIC) circuit for effective suppression of RF leakage from the transmit port to provide very high interport decoupling between transmit and receive ports. A compact antenna structure has been realized by using two-layered printed circuit board through vias interconnections of both receive ports of the antenna with inputs of SIC circuit. The validation model of proposed antenna offers more than 95 dB peak interport isolation. Moreover, the experimentally measured interport isolation is better than 70 dB throughout the antenna's 10 dB return-loss impedance bandwidth (BW) of 50 MHz (2.38–2.43 GHz). Furthermore, the recorded isolation is more than 80 dB in 20 MHz BW. The implemented antenna has good radiation characteristics including nice gain and low cross-polarization levels as endorsed by measurements. Same antenna structure with microstrip-T feeds can provide DC isolated ports with same interport RF isolation performance for active antenna applications. Such antenna with DC interport isolation will avoid the requirements of additional series capacitors on transmit and receive ports of antenna.